Taking Care Of Our Health Care Workers - Chee, Kwan Foong* (Social Health Analytics Sdn Bhd, 2024)
Despite potential challenges of the health care system, it is important for organisations to focus on work-life balance. This could include options for flexible work hours, better staff to decrease the chances of overworking, and encouraging vacations.